Quality of Life in Type 2 Diabetes Mellitus Patients: Calidad de vida en pacientes con diabetes mellitus tipo 2 | 2型糖尿病患者的生活质量 - Cadenillas-Maguiña, Nicole Solange (2024)
Introduction: Type 2 diabetes mellitus in the Americas affects approximately 62 million people, recognized as the most common chronic disease in the countries. It is estimated that by 2030, population growth, aging, urbanization, and lifestyle changes will lead to a 54% increase in diabetes, significantly impacting quality of life. Objective: To determine the level of quality of life among patients with type 2 diabetes mellitus in the Province of Barranca, Lima Region, Peru. Methods: Observational study with a descriptive design. The study population consisted of 242 patients attending a public hospital in the Province of Barranca, with a random sample of 144 patients. Data collection was conducted in the second quarter of 2021 through interviews using the WHOQOL-BREF questionnaire. Data analysis was performed using SPSS v.24 software. Results: 69% of the patients were female, aged between 40-64 years, with a mean age of 58 years. The quality of life was moderate (86%), with the social dimension rated as high (74%), while the physical dimension was rated as low (64%). When analyzed by gender, both males and females predominantly reported moderate quality of life, and when grouped by age, those over 65 years rated their quality of life as low (29%).